Broadband thin-film lithium niobate rapid adiabatic couplers enabling highly visible two-photon interference - Moon, Sunghyun; Lee, Jinil; Lee, Junhyung; Koh, Youngseo; Kim, Changhyun; Jang, Hyeong Soon; Kim, Sangin; Han, Sang Wook; Jung, Hojoong; Kwon, Hyounghan (Photonics Research, 2025)
The integrated quantum interferometer has provided a promising route for manipulating and measuring quantum states of light with high precision, requiring negligible optical loss, broad bandwidth, robust fabrication tolerance, and scalability. In this paper, a rapid adiabatic coupler (RAC) is presented as a compelling solution for implementing the integrated quantum interferometer on a thin-film lithium niobate (TFLN)-based platform, enabling a compact, broadband, and low-loss optical coupler. The TFLN-based RACs are carefully designed by manipulating a curvature along the structures with consideration of inherent birefringence as well as fabrication-induced slanted sidewalls. The high extinction ratio over 20 dB of the RAC-based Mach–Zehnder interferometer (MZI) is achieved in the wavelength range from 1500 to 1600 nm. The beam splitter (BS) with the balanced splitting ratio is exploited for observation of on-chip Hong–Ou–Mandel (HOM) interference with high visibility of 99.25%. We believe TFLN-based RACs hold great potential to be favorably utilized for integrated quantum interferometers, enabling widespread adoptions in myriad applications in integrated quantum optics.
Keywords: Adiabatic coupler; Broad bandwidths; High-precision; Lithium niobate; Optical-; Quantum interferometer; Quantum state; States of light; Thin-films; Two-photon interference